Opposite Roles for ZEB1 and TMEJ in the Regulation of Breast Cancer Genome Stability - Prodhomme, Mélanie K.; Péricart, Sarah; Pommier, Roxane M.; Morel, Anne-Pierre; Brunac, Anne-Cécile; Franchet, Camille; Moyret-Lalle, Caroline; Brousset, Pierre; Puisieux, Alain; Hoffmann, Jean-Sébastien; Tissier, Agnès (Frontiers in Cell and Developmental Biology, 2021)
Breast cancer cells frequently acquire mutations in faithful DNA repair genes, as exemplified by BRCA-deficiency. Moreover, overexpression of an inaccurate DNA repair pathway may also be at the origin of the genetic instability arising during the course of cancer progression. The specific gain in expression of POLQ, encoding the error-prone DNA polymerase Theta (POLθ) involved in theta-mediated end joining (TMEJ), is associated with a characteristic mutational signature. To gain insight into the mechanistic regulation of POLQ expression, this review briefly presents recent findings on the regulation of POLQ in the claudin-low breast tumor subtype, specifically expressing transcription factors involved in epithelial-to-mesenchymal transition (EMT) such as ZEB1 and displaying a paucity in genomic abnormality.